Fireside corrosion in biomass combustion plants - Coleman, K (Cranfield University, 2008)
In recent years concerns over global warming and escalating worldwide energy consumption have sparked an interest in C02-neutral energy sources for power production. Historically biomass-fired boilers have been operated at low steam temperatures (below 450°C) mainly for heat production. For electricity generation from fossil fuels maximum steam temperature of up to 620°C are used today. At these heat exchanger conditions there are severe high temperature corrosion issues when burning biomass. The potentially high levels of alkali chlorides and low levels of sulphates in deposits formed during combustion of biomass fuels can result in chemically aggressive low melting point deposits. The aim of this study was to investigate the effect of the combustion of biomass fuels on heat exchanger materials currently used in power generation. To achieve this a series of pilot scale combustion trials and laboratory corrosion tests have been carried out. The deposits formed during the combustion trials were analysed to identify their composition and provide a basis for the simulated deposits used in the corrosion 'testing. The corrosion testing investigated the effects of potential exposure conditions on the corrosion levels of the 5 candidate materials. The tests were carried out using simulated deposit compositions and gaseous environments (selected on the basis of potential fuel compositions). As well as weight change data, these tests yielded statistical data on actual metal loss from the materials allowing the performance of the material to be determined from dimensional metrology before and after exposure. Analysis of the data obtained has enabled an investigation into the sensitivity of the corrosion damage of the candidate heat exchanger materials to changes in temperature, gas environment and deposit composition. This has in tum permitted the development of an initial model for fireside corrosion damage of biomass combustion heat exchangers and identification of routes to improve this model.